Neural activity responsiveness by maturation of inhibition underlying critical period plasticity - Matsumoto, Ibuki; Nobukawa, Sou; Kanamaru, Takashi; Sakemi, Yusuke; Sviridova, Nina; Kurikawa, Tomoki; Wagatsuma, Nobuhiko; Aihara, Kazuyuki (Frontiers in Neural Circuits, 2025)
IntroductionNeural circuits develop during critical periods (CPs) and exhibit heightened plasticity to adapt to the surrounding environment. Accumulating evidence indicates that the maturation of inhibitory circuits, such as gamma-aminobutyric acid and parvalbumin-positive interneurons, plays a crucial role in CPs and contributes to generating gamma oscillations. A previous theory of the CP mechanism suggested that the maturation of inhibition suppresses internally driven spontaneous activity and enables synaptic plasticity to respond to external stimuli. However, the neural response to external stimuli and neuronal oscillations at the neural population level during CPs has not yet been fully clarified. In the present study, we aimed to investigate neuronal activity responsiveness with respect to the maturation of inhibition at gamma-band frequencies.MethodWe calculated inter-trial phase coherence (ITPC), which quantifies event-related phase modulations across trials, using a biologically plausible spiking neural network that generates gamma oscillations through interactions between excitatory and inhibitory neurons.ResultsOur results demonstrated that the neuronal response coherence to external periodic inputs exhibits an inverted U-shape with respect to the maturation of inhibition. Additionally, the peak of this profile was consistent with the moderate suppression of the gamma-band spontaneous activity.DiscussionThis finding suggests that the neuronal population's highly reproducible response to increased inhibition may lead to heightened synaptic plasticity. Our computational model can help elucidate the underlying mechanisms that maximize synaptic plasticity at the neuronal population level during CPs.